Interview with Manuel de Puelles Benítez - Ossenbach Sauter, Gabriela; Villalaín Benito, José Luis (Historia y Memoria de la Educación, 2015)
Interview with Manuel de Puelles Benítez, Professor of Educational Policy at the Universidad Nacional de Educación a Distancia (UNED) in Madrid since 1986. The interview addresses especially his academic activity in relation to the political history of education in Spain, but also his work in the Ministry of Education during the last years of the Franco dictatorship and the transition to democracy is discussed. Among other topics, Puelles has studied the birth of the Spanish education system in relation to the formation and consolidation of the modern nation-state, also debating political modernity and education throughout the twentieth century